Cellular pharmacokinetics and pharmacodynamics mechanisms of ginkgo diterpene lactone and its modulation of P‐glycoprotein expression in human SH‐SY5Y cells. (13th October 2019) - Liu, Jing‐ying; Geng, Ting; Duan, Kun; Gao, Xia; Huang, Chao‐jie; Wang, Jia‐jia; Huang, Wen‐zhe; Huang, Lou‐sheng; Wang, Zhen‐zhong; Xiao, Wei
Abstract: Ginkgo diterpene lactone (GDL) is the raw material for ginkgo diterpene lactone meglumine injection, which is used for treating cerebral ischemia. The aims of this study were to explore the cellular pharmacokinetics of GDL in whole cells and subcellular fractions, and detect cellular pharmacodynamics on the human SH‐SY5Y cells induced by oxygen–glucose deprivation and reoxygenation (OGD/R). Firstly, a simple, sensitive and reliable liquid chromatography–tandem mass spectrometry (LC–MS/MS) method was developed and validated for assessing the amount of ginkgolide A (GA), B (GB) and K (GK) in cellular/subcellular samples. Then, phosphatidylserine and mitochondria membrane potential were assayed to evaluate the extent of apoptosis effect. The study showed that the cellular/subcellular accumulation of GA and GB were increased in a concentration‐dependent manner; the levels of GA and GB in cytosol were the highest among these subcellular organelles. Meanwhile, GDL also attenuated the OGD/R‐induced increases in the percentage of apoptotic and mitochondria membrane potential. In addition, verapamil increased the rate and amount of GA and GB entering cellular/subcellular compartments through inhibition of P‐glycoprotein activity, and promoted the protective effect of GDL. The present study reports the cellular pharmacokinetics profiles of GA and GB in normal and OGD/R‐induced SH‐SY5Y cells in vitro for the first time, which provided valuable information for clinical safety application.